2021
DOI: 10.3390/ijerph182111364
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Medicine and Economics: A Proposal for Research Priorities Informed by a Case Series of Disease Reversal

Abstract: Chronic disease places an enormous economic burden on both individuals and the healthcare system, and existing fee-for-service models of healthcare prioritize symptom management, medications, and procedures over treating the root causes of disease through changing health behaviors. Value-based care is gaining traction, and there is a need for value-based care models that achieve the quadruple aim of (1) improved population health, (2) enhanced patient experience, (3) reduced healthcare costs, and (4) improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…It is estimated that in 2030, the percentage of incidence will achieve the value of about 40.5% [ 1 ]. Thus, CVDs constitute a strong challenge to public health [ 2 ]. However, progress has been achieved in the management of some CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that in 2030, the percentage of incidence will achieve the value of about 40.5% [ 1 ]. Thus, CVDs constitute a strong challenge to public health [ 2 ]. However, progress has been achieved in the management of some CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, medications for lowering lipid may be postponed till glycemic control is reached and a clearer representation of lipid pattern for patient is developed. (18) The link between higher ESR, LDL cholesterol, and lower HDL cholesterol may indicate low-grade inflammation causing cardiovascular risk. (19) Higher TG levels were linked to increased total leukocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…"Together, we must work to identify the social determinants of health; target prevention through multiple channels by identifying the intersections of various diseases; use data to understand the individuals and the populations we serve; be diligent about removing implicit bias and structural barriers; and harness technology to move health care from episodic, siloed 'sick care' to continuous and integrated 'healthcare'". 10 Preliminary studies 9,11,12 and systematic reviews 13 have demonstrated the effect of lifestyle medicine interventions. Dr. Richard Safeer provides a case study from Johns Hopkins Medicine later in this issue that describes a very compelling example.…”
mentioning
confidence: 99%
“…Preliminary studies 9,11,12 and systematic reviews 13 have demonstrated the effect of lifestyle medicine interventions. Dr. Richard Safeer provides a case study from Johns Hopkins Medicine later in this issue that describes a very compelling example.…”
mentioning
confidence: 99%